Willingness to stay of tourism lifestyle entrepreneurs: A configurational perspective - Dias, Á.; Silva, G. M. (Sustainability, 2021)
Tourism lifestyle entrepreneurs play an essential role in the innovation, sustainability, and competitiveness of tourism destinations. Thus, the ability of a destination to attract and retain this type of entrepreneur is an essential factor in strategic decisions. The limited research on this class of entrepreneurs implies that decision makers have little information about the factors that contribute to their willingness to stay in a particular destination. To address this challenge, this study employs a mixed-method approach, combining a quantitative survey-based study with a qualitative study by means of in-depth interviews. Based on survey data and using fuzzy set qualitative comparative analysis, this study identifies three equifinal configurations of antecedent factors (entrepreneurial self-efficacy, community-centered strategy, community attachment, and place attachment) that lead to a willingness to stay. Place attachment is the single-core condition. Moreover, the findings show that TLEs are not a homogeneous group. On the contrary, these entrepreneurs are driven by different motives and personal backgrounds. These results represent important insights for the definition of more sustainable strategies in destinations.